Kajian Semiotik Pada Sinematisasi Puisi Youtube Thefadlyma dan Relevansinya Pada Pembelajaran Menulis Puisi di Era Merdeka Belajar - Anggi Harinda; Muhamad Haryanto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research examines the cinematization of poetry on Thefadlyma's youtube channel by using a semiotic approach to analyze the signs in the videos Aku; Jatuh Hati and Selamat Jalan, Kanda. The purpose of this study is to describe how the semiotics of poetry cinematization on Thefadlyma's youtube channel and the relevance of the results of this study to poetry writing skills in the era of independent learning. The method used is descriptive qualitative, which focuses on icon, index, and symbol signs in accordance with Charles Sanders Pierce's semiotic analysis. The results show that the cinematization of poetry enriches the aesthetic experience and increases appreciation among the younger generation who are more connected to technology. In addition, this poetry cinematization is relevant in learning to write poetry, as it can be used as a medium that supports the development of students' creativity, self-expression, and writing skills. This research provides theoretical benefits by enriching semiotic literature in the context of digital poetry cinematization, as well as practical benefits for students, communities, and future researchers in understanding and applying semiotic concepts in poetry works in the digital era.